2020
DOI: 10.1024/0939-5911/a000670
|View full text |Cite
|
Sign up to set email alerts
|

Optimierungsbedarf von Spielersperren

Abstract: Zusammenfassung. Hintergrund und Fragestellung: Spielersperren stellen eine effektive Maßnahme des Spielerschutzes dar. Sie bedürfen jedoch einer Anpassung an die Bedürfnisse von Personen mit Glücksspielproblemen. Studien weisen auf Defizite hinsichtlich Sperrvorgang und -dauer sowie Zugangskontrollen hin. Ziel der qualitativen Untersuchung war es, Empfehlungen für die Optimierung von Spielersperren abzuleiten. Methodik: Mit semi-strukturierten Leitfäden wurden die am Prozess einer Spielesperre beteiligten Akt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…As problem gamblers are the target of SE measures, the effects on reducing gambling harm at the population level presumably remain low as long as the share of excluded problem gamblers among the total of problem gamblers is low. Fifth although studies investigating satisfaction with SE strategies reported generally positive ratings by the majority of respondents (39,40), the decision to self-exclude or not is an individual choice. Hence, the effectiveness of SE in reducing harm at the population level mainly hinges on the individual gambler's motivation.…”
Section: Self-exclusion: a Measure To Reduce Gambling Harm In The Pop...mentioning
confidence: 99%
“…As problem gamblers are the target of SE measures, the effects on reducing gambling harm at the population level presumably remain low as long as the share of excluded problem gamblers among the total of problem gamblers is low. Fifth although studies investigating satisfaction with SE strategies reported generally positive ratings by the majority of respondents (39,40), the decision to self-exclude or not is an individual choice. Hence, the effectiveness of SE in reducing harm at the population level mainly hinges on the individual gambler's motivation.…”
Section: Self-exclusion: a Measure To Reduce Gambling Harm In The Pop...mentioning
confidence: 99%